2014
DOI: 10.1016/j.tsf.2014.07.052
|View full text |Cite
|
Sign up to set email alerts
|

Surface photovoltage and modulation spectroscopy of E− and E+ transitions in GaNAs layers

Abstract: a b s t r a c tSurface photovoltage (SPV) spectra were measured for GaN 0.014 As 0.986 layers at room temperature and compared with room temperature photoreflectance (PR) and contactless electroreflectance (CER) measurements. Spectral features related to E − and E + transitions were clearly observed in SPV spectra at energies corresponding to PR and CER resonances. In this way it has been shown that SPV spectroscopy is an alternative absorption-like technique to study both the E − and E + transitions in dilute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In the context of the BAC model, it is worthwhile to comment on the optical transitions between the remaining bands predicted within this model. So far such transitions have been observed for dilute nitrides [35,[40][41][42][43] but they have never been clearly observed for dilute bismides. However in recent papers [17,20] the authors have observed some experimental evidences for Bi-related resonant states in the valence band in GaAs 1−x Bi x in the transient reflectivity and electroreflectance measurements.…”
mentioning
confidence: 99%
“…In the context of the BAC model, it is worthwhile to comment on the optical transitions between the remaining bands predicted within this model. So far such transitions have been observed for dilute nitrides [35,[40][41][42][43] but they have never been clearly observed for dilute bismides. However in recent papers [17,20] the authors have observed some experimental evidences for Bi-related resonant states in the valence band in GaAs 1−x Bi x in the transient reflectivity and electroreflectance measurements.…”
mentioning
confidence: 99%
“…SPV spectroscopy has seldom been used to study dilute nitride materials, e.g. the optical absorption (Bansal et al, 2006) and the band offset (Galluppi et al, 2005) in InGaAsN/GaAs single quantum wells and the E ̶ and E+ transitions in GaNAs layers (Kudrawiec et al, 2014). However, no other groups have reported on SPV investigations of GaAsSbN dilute nitride materials.…”
Section: Surface Photovoltage Characterizationmentioning
confidence: 99%
“…SPV spectroscopy has rarely been used in the investigations of dilute nitride materials. For example, it has been applied to investigate the optical absorption [36] and the band offset [37] in InGaAsN/GaAs quantum wells and the E − and E + transitions in GaAsN layers [38]. However, SPV investigations of quaternary GaAsSbN dilute nitride materials have not been reported.…”
Section: Introductionmentioning
confidence: 99%